HUBUNGAN KECEPATAN LARI DAN DAYA LEDAK OTOT TUNGKAI DENGAN HASIL LOMPAT JAUH SISWA SMP NEGERI 1 BUNUT - Defi, Defi; Slamet, Slamet; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to determine whether there is a significant relationship between running speed and leg muscle explosive power and long jump results in students of SMP Negeri 1 Bunut. This research was conducted in the field of SMP Negeri 1 Bunut JL. Arbes No. 42 Bunut, from July 2019 to July 2020 at the Bunut 1 Junior High School. This research is a type of correlational research (Correlation Research) and uses a total sampling technique (saturated sample), where the entire population is used as a sample. Based on the above sample determination, a sample of 20 people was obtained. From the calculation, it can be seen that the correlation value between speed and long jump is 0.122 smaller than r table = 0.444 meaning that there is no significant relationship. From the information above, it is obtained a correlation analysis between leg muscle strength and the long jump result, where the rtab is at a significant level α (0.05) = 0.444 means, rcount (0.488)> rtab (0.444), meaning that the hypothesis is accepted and there is a significant relationship. significant between leg muscle strength and long jump results in students of SMP Negeri 1 Bunut. The third hypothesis proposed and formulated is as follows: there is a significant (significant) relationship between the variable velocity (X1) and leg muscle strength (X2) together with the long jump result. The third hypothesis testing is done by using multiple correlation where rcount (0.535)> rtab (0.444).Key Words: Running Speed, Limb Muscle Explosive Strength, Long Jump Result